Kebijakan Pendidikan Implementasi Program Wajib Belajar 12 Tahun - Iis Margiyanti; Siti Tiara Maulia (Jurnal Pendidikan dan Sastra Inggris, 2023)
Education is an investment for the creation of quality Human Resources (HR). Through education, one can easily increase one's potential so that one can improve one's life in a better direction. Various efforts have been made by the Government to improve the quality and equity of education. One of the efforts is by holding a 12-year compulsory education program. The policy of the 12 year compulsory education program is expected to be able to succeed and improve the quality of human life. Writing this article using descriptive method and literature study. This research states that the 12-year compulsory education program in Indonesia has not run optimally. There are still areas that have not been able to implement the 12-year compulsory education program. As in Bogor district, which has not maximized the 12-year compulsory education program due to conditions that do not support access to education. Even so, the government continues to strive for this program to be realized properly. The government is trying to make strategies or steps that are expected to anticipate problems in education in Indonesia. This is evidenced by the success of the 12-year compulsory education program in Lampung, namely the large number of Lampung people who have successfully carried out education for 12 years, the large number of schools built in the city and in the interior as well as the participation of the Lampung people who support the implementation of this program..